Expression analysis of LlMYC2 during the development of microbulbs in Lilium lancifolium - SANG Qianzi; CHEN Yanzhu; PAN Wenqiang; ZHANG Mingfang; YANG Fengping; ZHANG Ting; LIU Zhongxu; DU Yunpeng; CAO Li (浙江大学学报. 农业与生命科学版, 2025)
MYC2 (myelocytomatosis protein 2) transcription factor is a member of the basic helix-loop-helix (bHLH) transcription factor family and is a key regulator of the jasmonate signaling pathway, which is involved in plant growth, development, and defense processes. In this study, the LlMYC2 gene of Lilium lancifolium was cloned, and the function and expression of this gene were analyzed to preliminarily explore the mechanism by which the LlMYC2 gene regulates the expansion ofthe microbulbs (bulblets and bulbils) in Lilium lancifolium. The results showed that the LlMYC2 gene is 2 148 bp in length, encodes 715 amino acids, has a molecular mass of 77.745 kDa, contains a typical MYC domain, and lacks the transmembrane domain. Phylogenetic tree analysis revealed that the LlMYC2 protein was the most closely related to the MYC2 proteins of Lilium regale and Lilium hybrid division Ⅶ. Subcellular localization results showed that LlMYC2 was a nucleus localized protein. Real time fluorogenic quantitative polymerase chain reaction (qRT-PCR) results showed that LlMYC2 was expressed in different tissues of Lilium lancifolium, with the highest expression level in the leaves, followed by the ovary, mature bulbils and mature bulblets. The expression level of LlMYC2 showed two distinct upregulation trends in the growth and development of microbulbs. Gene function verification results showed that after silencing LlMYC2 in Lilium lancifolium microbulbs, the expansion of bulblets and bulbils was inhibited. Treatment of mature bulbils with methyl jasmonate (MeJA) and its biosynthesis inhibitor salicylic acid hydroxamic acid (SHAM) affected the expression of LlMYC2. In summary, LlMYC2 is involved in the development of Lilium lancifolium microbulbs and the expansion of Lilium lancifolium microbulbs.